CD38 Facilitates Recovery from Traumatic Brain Injury - Levy, Ayelet (Mary Ann Liebert, Inc., 2009)
Traumatic brain injury (TBI) is a major cause of death and disability worldwide. It causes progressive tissue atrophy and consequent neurological dysfunctions. TBI is accompanied by neuroinflammation, a process mediated largely by microglia. CD38 is an ectoenzyme that promotes transmembrane signaling via the synthesis of potent calcium mobilizing agents or via its receptor activity. CD38 is expressed in the brain in various cell types including microglia. In previous studies, we showed that CD38 regulates microglial activation and response to chemokines. In view of the important role of neuroinflammation in TBI and the effects of CD38 on microglial responses, the present study examines the role of CD38 in the recovery of mice from closed head injury (CHI), a model of focal TBI. For this purpose, CD38-deficient and wild-type (WT) mice were subjected to a similar severity of CHI and the effect of the injury on neurobehavioral and cognitive functions was assessed by the Neurological Severity Score (NSS) and the Object Recognition Test, at various time points post-injury. The results show that recovery after CHI (as indicated by the NSS) was significantly lower in CD38-deficient mice than in WT mice and that the object recognition performance after injury was significantly impaired in injured CD38-deficient mice than in WT mice. In addition, we also observed that the amount of activated microglia/macrophages at the injury site was significantly lower in CD38-deficient mice compared with WT mice. Taken together, our findings indicate that CD38 plays a beneficial role in the recovery of mice from CHI and that this effect is mediated, at least in part, via the effect of CD38 on microglia responses.